Variations in Microbial Community on the Nutrient Content of Fermented Fish Feed Pellets with Tofu Waste - Endah Rita Sulistya Dewi; Ary Susatyo Nugroho; Ulfah Maria (Jurnal Biologi Tropis, 2022)
Tofu industrial waste has the potential to become an environmental pollutant when not treated optimally, so it needs proper treatment to minimize pollution. Fish farmers are expected to be able to innovate in terms of fish cultivation, so that harvest yields can be optimal to meet food needs. Furthermore, fermentation technology by Saccharomyces cerevisiae and Rhyzopus oligosporus are potential fungi that can increase the nutritional value of waste. This research aimed to produce an appropriate technology to produce fish feed pellets from fermented Saccharomyces cerevisiae and Rhyzopus oligosporus based on waste. This research method was designed in the form of research using a completely randomized design with 4 treatments (P0 without microbes); (P1 given Saccharomyces cerevisiae (2 gr) and Rhyzopus oligosporus (2 gr); (P2 Saccharomyces cerevisiae (1 gr) and Rhyzopus oligosporus (3 gr); (P3 Saccharomyces cerevisiae (3 gr) and Rhyzopus oligosporus (1 gr) with 3 replication.  The research results showed that: there was an effect of variation in microbial community on the nutrient content of the Fermented Fish Feed Pellets with Tofu Waste. Treatment P1 gave the highest protein and β -glucan content. Production of fermented fish feed pellets waste-based feed for catfish is the implementation of waste product, which can be further developed to meet the quality of the feed produced.